River conservation and management - Boon, P. J.; Raven, Paul J. (Hoboken : John Wiley & Sons, 2012)
This book is intended for those with an academic, scientific and practical interest in river conservation and management. It provides an overview of how changes in legislation, policies, institutional responsibilities, science, technology, practical techniques and public perception have influenced how rivers have been managed over the past 20 years and the challenges that lie ahead during the next 20 years. The book is based on the international conference River Conservation and Management:20 Years On held at York.
27 An Individual-Based Model of Swan-Macrophyte Conflicts on a Chalk River.
Print version record.
Keywords: Rivers -- Ecology; Rivers; Stream conservation -- Congresses; Environmental Studies; NATURE -- Animals -- Wildlife; SCIENCE -- Life Sciences -- Biological Diversity; Electronic books